Carbon Micron-size Content Dependency in Epoxy/Carbon Composite Coated onto SPCC Plate for Automotive Bodies Protection - Anggrainy, Rani; Susetyo, Ferry Budhi; Lubi, Ahmad; Yudanto, Sigit Dwi; Rosyidan, Cahaya; Soegijono, Bambang; Ajiriyanto, Maman Kartaman; Kurniawan, Ova; Nanto, Dwi (Science and Technology Indonesia, 2024)
Conventional epoxy coating for surface metal corrosion protection reported many unsolved technical problems. Adding filler in the epoxy could enhance the promising properties of the composite coating. Our work describes in detail the synthesizing and characterizing epoxy/carbon composite coating. Epoxy was mixed with thinner high gloss (HG) and hardener and stirred using a stirrer apparatus. After blending, various carbons were added (1 wt. %, 3 wt. %, and 5 wt. %) and then appropriately stirred. The different mixture composite was coated onto the steel plate cold rolled coiled (SPCC) plate using high-volume low-pressure (HVLP) in two passes. Various characterizations were performed, including crystallographic orientation, Infra-Red (IR)-spectra, surface morphology, thickness, hydrophobicity, hardness, and corrosion using X-ray diffraction (XRD), Fourier transform infrared (FTIR), Scanning electron microscopy (SEM), portable dry film coating thickness (DFT), digital camera, Vickers microhardness tester, and Potentiostat, respectively. More carbon micron-sized content led to elevate the peak intensity, surface bumpiness, and hydrophobicity. The uppermost external bumpiness and hydrophobicity values are 23.51 µm and 101◦. Hardness depends on carbon content and more carbon leads to an increase in the hardness of the composited coating. The highest average Vickers hardness value is 28.24 HV. The coating thickness influenced the corrosion rate, more coating thickness promoted lesser corrosion rate. The highest coating thickness (60.8 µm) promoted a corrosion rate of around 5.65×10−4 mmpy.